Effect of initial tangential intensity on the fluid dynamic characteristics in tangential burner - Pasymi; Wibisono Budhi Yogi; Bindar Yazid (MATEC Web of Conferences, 2017)
Swirl turbulent flow is intensively used by the industrial equipments such as combustion, separation and heat transfer equipments. The fluid dynamic characteristics of this flow are influenced by the chamber’s geometries and the operating conditions. One of the important operating condition variables which greatly affects the fluid dynamic characteristics is initial tangential intensity (ITI) or often known as swirl number. This study is aimed to quantify the effect of the initial tangential intensity on the fluid dynamic characteristics in a tangential burner. The method of the study is based on the computational fluid dynamic simulation under the Ansys Fluent CFD engine. The fluid dynamic characteristics were modeled using the standard k-ε turbulent model. The simulation results exhibited that the three dimensional flow structure in a tangential burner is dominated by the tangential flow. The fluid dynamic simulations also showed that the effect of the ITI on the mean turbulence intensity and the mean residence time begin to be significant at the ITI values ≥ 1.1 and ≥ 4.5 respectively, while at low ITI values, its effects on both variables are insignificant. The lowest pressure drop obtained in this study was found on the burner with ITI value of 3.2.